Designing Collaborative Learning Environment in Translator Training: An Empirical Research - Bayraktar-Özer, Özge; Hastürkoğlu, Gökçen (Research in Language, 2020)
The present study aims to investigate the efficacy of the collaborative learning method on the translation skills of students at the undergraduate level through a new model developed by the researchers. To this end, a pre-/post-test control group research design was followed to obtain empirical results in the translation of medical texts. The study group consisted of 60 undergraduate translation students in Turkey. Thirty students in the control group were instructed by using conventional training methods and each student worked individually. The completed translation was then evaluated by the instructor, as commonly applied in undergraduate translation programmes. The other 30 subjects in the experimental group were instructed through the collaborative learning method. The students participated in teamwork and undertook various roles such as terminologists, translators, proof-readers, and peer editors to check the final work. At the end of the three-week training, the difference between the translation performance scores of the two groups was found statistically significant in favour of the experimental group. The findings demonstrate the significant contribution of the collaborative learning method to the undergraduate students as this method provides them with an environment to improve the necessary translation skills for their future careers in terms of adopting different roles other than translators.